Palm oil and mineral oil based lubricants - their tribological and emission performance - Masjuki, H. H.; Maleque, Md. Abdul; Kubo, Aizoh; Nonaka, Tetsuya (Elsevier Inc., 1999)
A comparative study of wear, friction, viscosity, lubricant degradation and exhaust emissions was carried out on a palm oil and a mineral oil-based commercial lubricating oil. The wear and friction test was at first conducted using a reciprocating universal wear machine followed by a two-stroke gasoline Yamaha portable generator set, ET 950. The test conditions for the bench test were: pressure, 3.0 MPa; sliding speed, 0.20 m s21; sliding stroke, 80 mm; room temperature, >25°C. The test conditions for the actual engine were: constant load, 0.4 kW for wear of the piston ring but various loads for exhaust emissions and constant speed, 2800 rpm. Analysis of post bench test lubricating oils was performed using ISL viscometer, TAN/TBN analyzer and FT-IR spectroscopy to investigate viscosity, TAN value and the oxidation level, respectively. Exhaust emission analysis was also performed using a BOSCH exhaust gas analyzer. Experimental results demonstrated that the palm oil based lubricating oil exhibited better performance in terms of wears, and that the mineral oil based lubricating oil exhibited better performance in terms of friction. However, the palm oil based lubricant was the more effective in reducing the emmission levels of CO and hydrocarbon.